STRATEGI GURU DALAM PEMBENTUKAN KARAKTER SANTRI PONDOK PESANTREN AL-UM BENGKULU UTARA - Albetrik Meizontara; Alimni (STKIP Subang, 2023)
This research aims to identify the strategies used by teachers in shaping the character of students al the al-um islamic boarding school. The main aim of this relligious education instution is deal with moral and character issues. The research apprach applied is a desriptive method, using tool such as observation, interviwes annd documentation. The results show that the teacher use several strategies, including : 1, role models, 2. Habituation, 3. Delivery of advice.